Answer:
-7m(1.2m - 2) + (-6m) = -8.4m² + 8m
Step-by-step explanation:
Let us simplify the given expression
∵ The expression is -7m(1.2m - 2) + (-6m)
→ At first multiply the bracket by -7m
∵ -7m(1.2m - 2) = (-7m)(1.2m) - (-7m)(2)
∴ -7m(1.2m - 2) = -8.4m² - (-14m)
→ Remember (-)(-) = (+)
∴ -7m(1.2m - 2) = -8.4m² + 14m
→ Substitute it in the expression above
∵ -7m(1.2m - 2) + (-6m) = -8.4m² + 14m + (-6m)
→ Remember (+)(-) = (-)
∴ -7m(1.2m - 2) + (-6m) = -8.4m² + 14m - 6m
→ Add the like terms
∵ -7m(1.2m - 2) + (-6m) = -8.4m² + (14m - 6m)
∴ -7m(1.2m - 2) + (-6m) = -8.4m² + 8m